Nanomaterials and their composite scaffolds for photothermal therapy and tissue engineering applications. Issue 1 (31st December 2021) - Sun, Rui; Chen, Huajian; Sutrisno, Linawati; Kawazoe, Naoki; Chen, Guoping
ABSTRACT: Photothermal therapy (PTT) has attracted broad attention as a promising method for cancer therapy with less severe side effects than conventional radiation therapy, chemotherapy and surgical resection. PTT relies on the photoconversion capacity of photothermal agents (PTAs), and a wide variety of nanomaterials have been employed as PTAs for cancer therapy due to their excellent photothermal properties. The PTAs are systematically or locally administered and become enriched in cancer cells to increase ablation efficiency. In recent years, PTAs and three-dimensional scaffolds have been hybridized to realize the local delivery of PTAs for the repeated ablation of cancer cells. Meanwhile, the composite scaffolds can stimulate the reconstruction and regeneration of the functional tissues and organs after ablation of cancer cells. A variety of composite scaffolds of photothermal nanomaterials have been prepared to combine the advantages of different modalities to maximize their therapeutic efficacy with minimal side effects. The synergistic effects make the composite scaffolds attractive for biomedical applications. This review summarizes these latest advances and discusses the future prospects. Graphical abstract: uf0001